Research on women`s futsal: a scoping review - Barreira, J.; Pereira da Silva Junior, J. E.; Pereira de Souza, C. (Science and Medicine in Football, 2024)
The aim of this study was to conduct a comprehensive scoping literature review to provide an overview of the current state of research within women`s futsal. We searched four electronic databases (SPORTDiscus, PubMed, Scopus, and Web of Science) up to December 2023. Inclusion criteria comprised original research published in peer-reviewed journals, available in English, Spanish, or Portuguese. The focus was on studies investigating women in futsal, encompassing both players and those in leadership positions, regardless of their age or skill level. The analysis included the authorship (location), population characteristics (number of participants, level of play, and age), themes explored, and primary findings. A total of 692 records were found, but only 175 met the selection criteria. The results highlighted a recent attention in the scientific literature, with the first publications emerging in 2005 and a notable increase since 2016. Strength and Conditioning topics constituted the most frequently explored area, comprising 32% of the studies. Notably, no studies focusing on coaching or management aspects were identified. In terms of the participant population, most studies concentrated on high-level (33%) and senior (84%) players. Few studies have investigated practitioners with disabilities or women in other positions such as coaches or managers. Most of the studies were conducted by Brazilian researchers (60%), indicating the need for investigations in different socio-cultural contexts. The recent academic attention and the upcoming inaugural edition of the FIFA Futsal Women`s World CupTM in 2025 reinforce the need for further studies on women`s futsal. This review contributes by identifying the scientific gaps that can be explored by future investigations.